Sustainable Green Hydrogen Generation from Biomass Waste: Technologies and Environmental Impact - Bengharbia, Iman; Alnass, Yousef; Younus, Tahani Abdulrraziq Ahmeedah (AlQalam Journal of Medical and Applied Sciences, 2025)
This study assesses the potential of sustainable green hydrogen production from biomass waste as a renewable energy source for low-carbon economies. Among the technologies analyzed, gasification, pyrolysis, anaerobic digestion, and dark fermentation—gasification and anaerobic digestion emerge as the most viable, meeting 20–50% of regional hydrogen demand. Life cycle analysis highlights substantial benefits, including reduced greenhouse gas emissions, energy efficiency, and effective waste valorization. However, challenges persist in terms of technological efficiency and economic scalability. The study underscores the critical role of biomass-based hydrogen in sustainable energy systems. It identifies future priorities such as catalyst development for tar reduction and AI-driven supply chain optimization to overcome technical and policy barriers.